Role of astrocyte–synapse interactions in CNS disorders - Blanco‐Suárez, Elena (J Physiol, 2016)
Astrocytes comprise half of the cells in the brain. Although astrocytes have traditionally been described as playing a supportive role for neurons, they have recently been recognized as active participants in the development and plasticity of dendritic spines and synapses. Astrocytes can eliminate dendritic spines, induce synapse formation, and regulate neurotransmission and plasticity. Dendritic spine and synapse impairments are features of many neurological disorders, including autism spectrum disorder, schizophrenia, and Alzheimer's disease. In this review we will present evidence from multiple neurological disorders demonstrating that changes in astrocyte–synapse interaction contribute to the pathologies. Genomic analysis has connected altered astrocytic gene expression with synaptic deficits in a number of neurological disorders. Alterations in astrocyte‐secreted factors have been implicated in the neuronal morphology and synaptic changes seen in neurodevelopmental disorders, while alteration in astrocytic glutamate uptake is a core feature of multiple neurodegenerative disorders. This evidence clearly demonstrates that maintaining astrocyte–synapse interaction is crucial for normal central nervous system functioning. Obtaining a better understanding of the role of astrocytes at synapses in health and disease will provide a new avenue for future therapeutic targeting. [Image: see text]